2013
DOI: 10.1007/s00586-013-2895-1
|View full text |Cite
|
Sign up to set email alerts
|

Simple prediction method of lumbar lordosis for planning of lumbar corrective surgery: radiological analysis in a Korean population

Abstract: This simple calculation method can provide a more appropriate and simpler prediction of lumbar lordosis for Asian populations. The prediction of lumbar lordosis should be used as a reference for surgeons planning to restore the lumbar lordosis in lumbar corrective surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…The importance of maintenance or restoration of spinopelvic balance cannot be understated with numerous works demonstrating the correlation of quality of life measures with spinal parameters (Schwab et al, ; Takemoto et al, ; Kyrola et al, ; Protopsaltis et al, ). There are also numerous formulae to predict ideal lordosis on the basis of PI (Legaye and Duval‐Beaupere, ; Vialle et al, ; Rose et al, ; Schwab et al, ; Lee et al, ; Xu et al, ; Yamato et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of maintenance or restoration of spinopelvic balance cannot be understated with numerous works demonstrating the correlation of quality of life measures with spinal parameters (Schwab et al, ; Takemoto et al, ; Kyrola et al, ; Protopsaltis et al, ). There are also numerous formulae to predict ideal lordosis on the basis of PI (Legaye and Duval‐Beaupere, ; Vialle et al, ; Rose et al, ; Schwab et al, ; Lee et al, ; Xu et al, ; Yamato et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that one article reported an overcorrection of lumbar lordosis (LL) as an effective treatment modality to maintain optimal sagittal alignment in patients with degenerative lumbar kyphosis, it should be considered in preoperative planning for patients with adult spinal deformity and sagittal imbalance. 10 The primary goal of the surgical correction described in this study was to achieve an ideal LL, with a theoretical value calculated according to the Korean version of Legaye's formula (sacral slope [SS] = 0.80+0.74 pelvic incidence, lower LL = 5.20 +0.87 SS, maximal LL = 17.41+0.96 SS), as reported by Lee et al [10][11][12] In our case study, according to this formula, the highest and lowest LL in the patient were -57.97° and -41.94°, respectively. Therefore, in the first operation performed on our patient, Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Several formulas have been created to evaluate the ideal LL to be reestablished in lumbar fusion surgery in different populations. Based on Legaye's formula in Korean patients [18] , Lee et al [9] found that overcorrection of LL (postoperative LL angle > ideal LL) effectively maintains the optimal SVA in patients with degenerative lumbar kyphosis during a minimum 2-year follow-up. Considering the effect of age, Xu et al [19] determined the predictive formula for the ideal LL in Chinese adults as: LL = 0.508 × PI -0.088 × age + 28.6.…”
Section: Discussionmentioning
confidence: 99%